Cause of neonatal deaths in Northern Ethiopia: a prospective cohort study - Hayelom Gebrekirstos Mengesha; Berhe W. Sahle (BMC, 2017)
Abstract Background Despite the significant reduction in childhood mortality, neonatal mortality has shown little or no concomitant decline worldwide. The dilemma arises in that the lack of documentation of cause of death in developing countries, where registration of vital events is virtually nonexistent. Understanding of the causes of death in neonates is important to guide public health interventions. The present study identifies the common causes of neonatal death in Ethiopia. Methods A prospective cohort study was conducted among neonates born between April 2014 and July 2014 in seven hospitals, in Tigray region, Ethiopia. Mothers were interviewed by midwifes respecting risk factors and infant survival. For neonates who died in hospital, causes of death were extracted from medical records, whereas a verbal autopsy method provided presumptive assignment of cause of death for those infants who died at home. Results Of the1152 live births, there were 68 deaths (63 per 1000 live births). Two thirds of deaths were attributable to prematurity 23 (34%) or asphyxia 21 (31%). Slight variance was seen between the morality patterns in early and late neonatal periods. In the early neonatal period, 37% were due to prematurity, while asphyxia (35%) was more common in the late neonatal period. All infection-related deaths occurred in neonate-mother dyads from rural areas. Conclusion Prematurity, asphyxia, and infections were the leading causes of neonatal deaths in Tigray region during the study period. Causes of deaths identified during early and late neonatal mortality differed, which clearly indicates the need for responsive and evidence-based interventions and policies.